Assessing the impacts of China's environmental tax using a dynamic computable general equilibrium model - Li, Gen; Masui, Toshihiko (Journal of cleaner production, 2019)
Since 2018, China has put into practice the new Environmental Protection Tax Law, which levies taxes on non-greenhouse pollutants with stringent standards. To fully study the socioeconomic and environmental impacts of this policy, this paper establishes a dynamic country-level Compute General Equilibrium (CGE) model with the electricity sector disaggregated into 5 technologies and 19 major taxable pollutants included. Five scenarios are developed, including the baseline scenario BaU, the low environmental tax scenario LowET, the high environmental tax scenario HighET, the low environmental tax and low carbon tax scenario LowETC, and the high environmental tax and high carbon tax scenario HighETC. The simulation results show that the environmental tax could help reduce emissions of most kinds of pollutants but bring negative effects on the Gross Domestic Product (GDP). Compared to the BaU scenario, the GDP loss by 2030 would be 0.10%, 0.21%, 0.32% and 0.67% in the LowET, HighET, LowETC and HighETC scenarios. The emission of sulphur dioxide (SO2) will decrease by 3.55%, 7.15%, 6.70% and 13.01%, and the emission of carbon dioxide (CO2) will be reduced by 2.21%, 4.62%, 8.91% and 16.77%. The result also shows that the heavy polluted sectors and energy-intensive sectors will suffer higher output loss, while the clean energy sectors and service sector will experience an increase in the output in the policy scenarios. •The environmental tax could help reduce emissions of most kinds of pollutants.•The GDP loss would vary from 0.10% to 0.67% under different tax levels.•Heavy polluted or energy-intensive sectors will suffer higher output loss.•The environmental tax has a synergy effect of reducing carbon emissions.